2013
DOI: 10.13045/acupunct.2013043
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Study about Qualitative and Quantitative Characteristics of Acupuncture Sensation According to the Type of Pharmacopuncture: Study about BUM Pharmacopuncture, Mountain Ginseng Pharmacopuncture and Sciatica No. 5 Pharmacopuncture

Abstract: Objectives : This study was designed to find out the differences of the acupuncture sensation by type of pharmacopuncture. And furthermore we try to find out whether normal saline(NS) is able to be constituted as an appropriate control group for the Calculus Bovis • Fel Ursi ․ Moschus(BUM) pharmacopuncture, mountain ginseng pharmacopuncture and sciatica no. 5 pharmacopuncture. Methods : NS and three type of pharmacopunctures were inserted into ST36, and ST37 of the subjects. Before and after the treatment, sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
(6 reference statements)
0
1
0
1
Order By: Relevance
“…In the healthy subjects, intravenous injection of wild ginseng pharmacopuncture did not change the blood pressure, pulse, temperature, respiration, and blood test indexes [18,19]. Wild ginseng pharmacopuncture injected at acupoints (ST36 and ST37) did not significantly change the acupuncture sensations as compared with other types of complex-herb pharmacopuncture (e.g., BUM pharmacopuncture made of Calculus Bovis, Fel Ursi, Moschus) and saline injection [20]. Another study showed that only the volume of injected solution, but not the stimulation methods (perpendicular versus transverse injection) at acupoints, affected the subjective intensity reporting of pharmacopuncture stimulation [21].…”
Section: Physiological Response To Ginseng Pharmacopuncture In Human mentioning
confidence: 99%
“…In the healthy subjects, intravenous injection of wild ginseng pharmacopuncture did not change the blood pressure, pulse, temperature, respiration, and blood test indexes [18,19]. Wild ginseng pharmacopuncture injected at acupoints (ST36 and ST37) did not significantly change the acupuncture sensations as compared with other types of complex-herb pharmacopuncture (e.g., BUM pharmacopuncture made of Calculus Bovis, Fel Ursi, Moschus) and saline injection [20]. Another study showed that only the volume of injected solution, but not the stimulation methods (perpendicular versus transverse injection) at acupoints, affected the subjective intensity reporting of pharmacopuncture stimulation [21].…”
Section: Physiological Response To Ginseng Pharmacopuncture In Human mentioning
confidence: 99%
“…기존 침치료의 자극량에 대해서는 여러 연구 [4][5][6][7] 가 이루 어진 반면, 약침치료의 자극량에 대해서는 약침종류와 득기 에 관한 연구 [8][9][10] 가 이루어져 있으나, 특히 약침 주입량과 자입 방법에 대해서는 연구가 부족하다.…”
Section: ⅰ 서 론unclassified